"The role of the Military-Social Work discipline in the future professional activity of civil-military cooperation service specialists" - Myalo , V. (Problems of Engineer-Pedagogical Education, 2023)
This study focuses on identifying the significance of the Military-Social Work discipline in fostering civil-military cooperation and facilitating effective practices in military-social work. The modern views of scientists on the state of social security of servicemen and members of their families, as well as the experience of military-social work in Ukraine, are analyzed. The potential for establishing adequate social support for servicemen and their families through civil-military cooperation to enhance the efficacy in the military sphere is examined. It is emphasized that the military social environment has a serious impact on well-being, physical and psychological health, work capacity and the formation of a clear system of values of military personnel. In this connection, the main problems faced by military personnel and their family members are considered. The main directions and principles on which military social work is based are analyzed. It is concluded that military social work is important for the development of effective approaches, forms, technologies and methods of social management in the National Guard of Ukraine. It is concluded that the discipline of Military-Social Work plays an important role in the formation of social competence of future officers. The article aims to consolidate the accumulated experience in social work and the development of social competence for its efficient application among military personnel and their families, drawing from both domestic and international historical perspectives. It further explores the potential application of this experience within the context of civil-military cooperation. The article defines the types, forms and content of social work carried out by state and non-state social services in the community, as well as military-social work with servicemen and their family members. The article examines the possibilities of using and combining resources available in Ukraine today to improve social standards and provide social guarantees to servicemen and their family members. The necessity of cultivating social competence among future officers through the study of Military-Social Work is substantiated.